Pedagogical Journeys through World Politics
XLII, 296 p.
Keywords: This edited volume is a collection of twenty-three autobiographical narratives by successful teachers of global politics and international relations. The diverse contributors (from a variety of institutional contexts, sub-disciplines, and countries) describe their development as teachers, articulate mission statements for their teaching, and link both to pedagogical practices that exemplify their teaching philosophies. Rather than provide specific recipes for authoritative techniques, the essays empower readers as creative developers of their own approaches to teaching global politics. They demonstrate the multiple ways that instructors have grounded deliberate pedagogical designs in a variety of deeper philosophical commitments, and resources are provided to facilitate discussion and collaborative deliberation between groups of readers. Jamie Frueh is Professor of History and Political Science at Bridgewater College, USA. As Director of the Center for EngagedLearning, he oversees Bridgewater’s interdisciplinary academic programs and four endowed institutes. He runs pedagogy workshops at home and abroad, and is the 2019 recipient of the International Studies Association’s Deborah Gerner Innovative Teaching Award.